The Influence of Islamic Work Ethics and Work Environment on Generation Z Employee Performance Through Work Motivation as a Mediating Variable - Andika Jani Alkautsar; Suhartini, Suhartini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of Islamic Work Ethics and Work Environment on the Performance of Generation Z Employees Through Work Motivation as a Mediating Variable. The method used in this study is a quantitative approach with data collection techniques through questionnaires. The sample in this study consisted of 149 respondents who were Generation Z employees who were Muslim. Data analysis was carried out using Structural Equation Modeling (SEM) with the help of SmartPLS 3 software. Hasil penelitian menunjukkan bahwa Etika Kerja Islam dan Lingkungan Kerja mempunyai pengaruh positif dan signifikan terhadap kinerja karyawan. Islamic Work Ethics has a positive and significant influence on Work Motivation, but the work environment does not have an influence on Work Motivation. Work Motivation has a positive and significant influence on Employee Performance, but Work Motivation is not proven to be a mediating variable between Islamic Work Ethics and Work Environment on Employee Performance.